Phytochemicals and Biological Activities of Garcinia morella (Gaertn.) Desr.: A Review - Murthy, Hosakatte Niranjana (Molecules, 2020)
Garcinia morella (Gaertn.) Desr. is an evergreen tree that yields edible fruits, oil, and resin. It is a source of “gamboge”, a gum/resin that has a wide range of uses. The fruits, leaves, and seeds of this tree are rich in bioactive compounds, including xanthones, flavonoids, phenolic acids, organic acids, and terpenoids. Evidence from different studies has demonstrated the antioxidant, antifungal, antiviral, hepatoprotective, anticancer, anti-inflammatory, antibacterial, and larvicidal activities of the fruit, leaf, and seed extracts of G. morella. This review summarizes the information on the phytochemicals of G. morella and the biological activities of its active constituents.